Direct Shear Strength of Clay Reinforced with Coir Fiber - Anita Widianti; Willis Diana; Maratul Hasana (U Karst, 2020)
Indonesia is the largest coconut producing country in the world. However, the resulting coir waste is still rarely used for structural materials. This research studied the effect of random inclusion of coir fiber on the shear strength of clay with high plasticity. The carried test in this study is a direct shear strength test. The fiber content variations used are 0%, 0.25%, 0.50%, 0.75%, and 1% of the dry weight of the mixture with a fiber length of between 30 mm to 50 mm. The results show that the reinforcement of coir fiber can increase the cohesion and friction angle. The maximum increase in cohesion value was obtained at fiber content of 0.75%, which was 39.66%. The increase in the value of the friction angle was obtained at 1% fiber content, which was 46.67%. The optimum coir fiber content was achieved at the fiber content of 0.75%. With this content, the value of the shear strength reaches its maximum with an increase of 39.4% at a normal stress of 8.071 kPa.